2001
DOI: 10.1097/00003246-200111000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine administration reduces Gram-negative bacteremia in severely burned patients: A prospective, randomized, double-blind trial versus isonitrogenous control

Abstract: Significantly fewer bacteremic episodes with Gram-negative organisms occurred in the glutamine-supplemented patients. Glutamine supplementation improved measures of nutrition and decreased measures of overall inflammation. In addition, a trend toward lower mortality rate, decreased overall bacteremia incidence, and antibiotic usage in the glutamine group was observed. Glutamine's beneficial effects may be a result of improved gut integrity or immune function, but the precise mechanism of glutamine's protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
155
1
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(176 citation statements)
references
References 17 publications
7
155
1
13
Order By: Relevance
“…Several controlled trials in specific subgroups of postsurgical and other types of patients have shown beneficial clinical or metabolic effects when GLN is added to PN. 25,[31][32][33][34][35]39,41,42 These studies have incorporated L-GLN doses in PN ranging from 0.29 to 0.57 g/kg/d, 25,[31][32][33][34][35]39 and alanyl-GLN dipeptide doses similar to the dose used in the current trial (0.40-0.50 g/kg/d or equivalent to 0.26-0.33 g of L-GLN/kg/d). However, several trials also show no benefits, possibly attributable to differences in study patient clinical characteristics and degree of GLN depletion within and between studies, as well as the dose of parenteral GLN used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several controlled trials in specific subgroups of postsurgical and other types of patients have shown beneficial clinical or metabolic effects when GLN is added to PN. 25,[31][32][33][34][35]39,41,42 These studies have incorporated L-GLN doses in PN ranging from 0.29 to 0.57 g/kg/d, 25,[31][32][33][34][35]39 and alanyl-GLN dipeptide doses similar to the dose used in the current trial (0.40-0.50 g/kg/d or equivalent to 0.26-0.33 g of L-GLN/kg/d). However, several trials also show no benefits, possibly attributable to differences in study patient clinical characteristics and degree of GLN depletion within and between studies, as well as the dose of parenteral GLN used.…”
Section: Discussionmentioning
confidence: 99%
“…Our infection data are consistent with previous studies showing a beneficial effect of GLN-supplemented PN to decrease nosocomial infections in other types of critically ill patients. 31,[39][40][41][42] S aureus is responsible for a high percentage of nosocomial infections in postsurgical and ICU patients. [1][2][3][4][5] Our data show for the first time that GLN-supplemented PN specifically reduces infections attributed to S aureus, fungi, and enteric Gram-negative bacteria, which were markedly decreased with GLN-PN in the nonpancreatic surgery cohort ( Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Critical illness PN de Beaux et al (14) Déchelotte et al (15) Estivariz et al (16) Fuentes-Orozco et al (18) Fuentes-Orozco et al (17) Griffiths et al (21) Ockenga et al (33) Perez-Barcena et al (36) Sahin et al (38) Wischmeyer et al (42) Subtotal (95 % CI) Total events: 104 (treatment), 136 (control) Test for heterogeneity: χ 2 12·9, df 9 (P=0·17), I 2 30·4 % Test for overall effect: Z 2·24 (P=0·03)…”
Section: Methodsmentioning
confidence: 99%
“…One study in patients with burns (Wischmeyer et al 2001) has used parenteral glutamine independently of the method of feed administration with good effect on infectious complications. This approach to parenteral administration independent of the route of feeding appears very promising and needs testing in a wider critical-care setting.…”
Section: Glutamine and Its Effect On Heat-shock Proteinsmentioning
confidence: 99%